‘It’s all about flexibility!’ A case study on telework in a Portuguese company after the COVID-19 pandemic - Rita Grave; Sara Isabel Magalhães; Cátia Pontedeira; Ana Luísa Patrão; Ana R. Pinho; Liliana Rodrigues; Conceição Nogueira (Humanities & Social Sciences Communications)
Abstract This study aims to understand how teleworking practices are implemented and developed in a Portuguese company after the COVID-19 pandemic, seeking to assess their gender dimension when balancing professional and family dynamics. Based on a case study, including 11 semi-structured interviews with the institution’s managers, four themes emerged: The company’s approach to telework; Telework: From COVID-19 to the ‘new normal’; The cultural conservatism of mistrust; Hybrid regime, matching interests. These results are accompanied by gender inequalities with impacts on women’s well-being due to the added tasks of housework or caregiving. To conclude, telework is here to stay with improvements towards flexwork.